Impact of training on flight time in female volleyball players aged 13-14 years - Blerina Mema; Enkeleida Lleshi; Entela Kushta (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Vertical jump is a fundamental element of volleyball performance, particularly for young athletes whose physical development is still in progress.